Toy for boys ... and girls - Stott, M. J.. (Swimming World Magazine, 2018)
Thanks to new and innovative equipment for training, today`s swimmers have enjoyed more productive workouts, resulting in faster swimming. ... Zum Einsatz verschiedener Geräte und Trainingsmittel im Training der Schwimmer des Fort Collins Area Swim Team.